PHYSICAL CONTROLS ON THE SALINITY OF MID-OCEAN RIDGE HYDROTHERMAL VENT FLUIDS - Fontaine F.J.; Wilcock W.S.D.; Butterfield D.A. (My University, 2007)
Variations in the salinity of black smoker effluents (0.1-~ 8 wt.% NaCl) relative to seawater (3.2 wt.% NaCl) are attributed to phase separation and segregation of the resulting brines and vapors. However, models of phase separation predict brines with substantially higher salinities than observed at vents and such brines are commonly observed in fluid inclusions from fossil hydrothermal systems. It has been postulated that the range of observed salinities is controlled by the density of upwelling fluids. Here we present models of hydrothermal circulation that predict the observed maximum salinity when an upper layer of high-permeability is included, and also reproduce black smoker temperatures when the upflow zone is surrounded by a low-permeability shell. Pressure gradients across the permeability boundary act as a density filter impeding the passage of high-salinity fluids, while the shell provides sufficient insulation to tap hot fluids to the surface. Our models fit the observations when the permeabilities of the upper layer differ from the permeability of the lower layer by factors of ~ 10 and ~ 100 in upflow and downflow regions, respectively, and when the permeability of the shell is one tenth that of the lower layer. The permeability structure we propose is consistent with observations in oceanic crust and inferences from ophiolites. While a previous study argues that black smoker temperatures are a consequence of the thermodynamic properties of seawater, our work suggests that very specific permeability configurations are required to match both the temperature and maximum salinity. © 2007 Elsevier B.V. All rights reserved.
Keywords: HYDROTHERMAL SYSTEMS; MID-OCEAN RIDGES; NUMERICAL MODELING; SALINITY